1988
DOI: 10.1016/0014-5793(88)80400-9
|View full text |Cite
|
Sign up to set email alerts
|

Brain natriuretic factor Augmentation of cellular cyclic GMP, activation of particulate guanylate cyclase and receptor binding

Abstract: The newly discovered peptide, brain natriuretic factor (BNF), caused a concentration-dependent increase (up to 400-fold) in intracellular cyclic GMP levels in cultured endothelial, smooth muscle and fibroblast cells. The extent of cGMP augmentation was comparable to that produced by atria1 natriuretic factor (ANF). The activity of the membrane-bound guanylate cyclase of different rat tissues and cultured cells was markedly stimulated by the peptide and the addition of ATP potentiated the stimulation. As oppose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…Subsequently, addition of exogenous ATP to the reaction was reported to further increase ANP-dependent guanylyl cyclase activity (8,24,41). Similar stimulatory effects of ATP were reported for the intestinal and retinal guanylyl cyclases as well (17,42,44).…”
mentioning
confidence: 55%
“…Subsequently, addition of exogenous ATP to the reaction was reported to further increase ANP-dependent guanylyl cyclase activity (8,24,41). Similar stimulatory effects of ATP were reported for the intestinal and retinal guanylyl cyclases as well (17,42,44).…”
mentioning
confidence: 55%
“…It has been suggested that, like ANP and BNP, volume overload may be a stimulus for synthesis and secretion of AM by vascular endothelial [21]and smooth muscle cells [22], despite the differences in their intracellular signaling systems [9, 23, 24, 25, 26]. In addition, it has been reported that the failing ventricular myocardium itself may be a source of increased AM production [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…cGMP PDE activity was assayed according to the method of Torres et al (27). Cytosolic fractions of IMCD cell homogenates, collected as described (10)(11)(12)(13)(14)(15) Values are means±SEM. Significant difference versus control rats is indicated by * P < 0.01, and * P < 0.05.…”
Section: Introductionmentioning
confidence: 99%
“…ANPR-C, also known as the ANP clearance receptor, does not signal through activation of guanylyl cyclase, but may serve as a clearance receptor for natriuretic peptides; it may also function through intermediate guanine nucleotide regulatory proteins to inhibit adenylyl cyclase (11). While ANPR-A and ANPR-B have rather strict structural requirements for ligand binding (12)(13)(14)(15), ANPR-C has less rigorous structural requirements and binds the internally deleted analogues of ANP (c-ANP) (12,(16)(17)(18), compounds which do not activate the membrane guanylate cyclase.…”
Section: Introductionmentioning
confidence: 99%